Treatment for anxiety using spiritual emotional freedom technique - Rima Pratiwi Fadli; Yola Eka Putri; Berru Amalianita; Nilma Zola; Ifdil Ifdil (RedWhite Press, 2020)
This study aims to describe SEFT and treatment in the treatment of anxiety. This study used rapport cases on three clients. The research instrument used is rapport Client Case, observation and depression, Anxiety, and Stress Scale. The data obtained were analyzed by T-Test Statistic Nonparametric Wilcoxon Signed-Rank Test. The findings from the study showed that before treatment, the level of anxiety at very heavy levels and after the treatment became mild and normal. Based on T-test results found that there is a significant difference in anxiety level of clients before and after treatment. This means SEFT is effective for reducing client anxiety.